If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 = -2u(u + 6) + -9 Reorder the terms: -10 = -2u(6 + u) + -9 -10 = (6 * -2u + u * -2u) + -9 -10 = (-12u + -2u2) + -9 Reorder the terms: -10 = -9 + -12u + -2u2 Solving -10 = -9 + -12u + -2u2 Solving for variable 'u'. Combine like terms: -10 + 9 = -1 -1 + 12u + 2u2 = -9 + -12u + -2u2 + 9 + 12u + 2u2 Reorder the terms: -1 + 12u + 2u2 = -9 + 9 + -12u + 12u + -2u2 + 2u2 Combine like terms: -9 + 9 = 0 -1 + 12u + 2u2 = 0 + -12u + 12u + -2u2 + 2u2 -1 + 12u + 2u2 = -12u + 12u + -2u2 + 2u2 Combine like terms: -12u + 12u = 0 -1 + 12u + 2u2 = 0 + -2u2 + 2u2 -1 + 12u + 2u2 = -2u2 + 2u2 Combine like terms: -2u2 + 2u2 = 0 -1 + 12u + 2u2 = 0 Begin completing the square. Divide all terms by 2 the coefficient of the squared term: Divide each side by '2'. -0.5 + 6u + u2 = 0 Move the constant term to the right: Add '0.5' to each side of the equation. -0.5 + 6u + 0.5 + u2 = 0 + 0.5 Reorder the terms: -0.5 + 0.5 + 6u + u2 = 0 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + 6u + u2 = 0 + 0.5 6u + u2 = 0 + 0.5 Combine like terms: 0 + 0.5 = 0.5 6u + u2 = 0.5 The u term is 6u. Take half its coefficient (3). Square it (9) and add it to both sides. Add '9' to each side of the equation. 6u + 9 + u2 = 0.5 + 9 Reorder the terms: 9 + 6u + u2 = 0.5 + 9 Combine like terms: 0.5 + 9 = 9.5 9 + 6u + u2 = 9.5 Factor a perfect square on the left side: (u + 3)(u + 3) = 9.5 Calculate the square root of the right side: 3.082207001 Break this problem into two subproblems by setting (u + 3) equal to 3.082207001 and -3.082207001.Subproblem 1
u + 3 = 3.082207001 Simplifying u + 3 = 3.082207001 Reorder the terms: 3 + u = 3.082207001 Solving 3 + u = 3.082207001 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + u = 3.082207001 + -3 Combine like terms: 3 + -3 = 0 0 + u = 3.082207001 + -3 u = 3.082207001 + -3 Combine like terms: 3.082207001 + -3 = 0.082207001 u = 0.082207001 Simplifying u = 0.082207001Subproblem 2
u + 3 = -3.082207001 Simplifying u + 3 = -3.082207001 Reorder the terms: 3 + u = -3.082207001 Solving 3 + u = -3.082207001 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + u = -3.082207001 + -3 Combine like terms: 3 + -3 = 0 0 + u = -3.082207001 + -3 u = -3.082207001 + -3 Combine like terms: -3.082207001 + -3 = -6.082207001 u = -6.082207001 Simplifying u = -6.082207001Solution
The solution to the problem is based on the solutions from the subproblems. u = {0.082207001, -6.082207001}
| T=5g+5u | | 4+y=-2 | | (x^2+16x+55)=0 | | 2+y=-3 | | X^4-7x^2-8=0 | | 125v^3+27g^3= | | 3x+15=6x-4 | | 40x=25x+1 | | -2(m-7)-5(-5m-8)=22(m+3)-7 | | 9x-63=63x+63 | | 2x-4=34 | | 6+y=-4 | | 25x^2+14=0 | | 25x^2= | | 22h+9=97 | | -40x-8=21 | | 20y+9=149 | | x^2-2x=18 | | 25x^2-14=0 | | 2x-93=-10x+51 | | 6-(3y-9)=8-4y | | 3x(5-9)= | | 10(420-v)+12v=420(11) | | 13x-9+2x-3=12x-4+2x | | n-8=9 | | 16x+7=19x+10 | | -2(m-7)-5(-5m-8)=22(m+3)7 | | 4y-5y+8y= | | 10h+8=78 | | x^3+3x-10=0 | | (27x^3-1)=0 | | =3+(n-1)4 |